Efektivitas Model Pembelajaran Kooperatif Brainstroming Dengan Desain Pembelajaran Kemp Pada Mata Pelajaran Fiqih SMP Al-Qonita Palangka Raya - Almadani, Teguh; Jasiah (STAI Tebing Tinggi Deli, 2025)
This study aims to improve student learning activities in Accounting subjects and evaluate students' responses to the application of the Think Pair Share type cooperative learning model in class XI IPS 1 SMA Negeri 2 Wonosari for the 2011/2012 school year. This study uses the Classroom Action Research (PTK) method which is carried out in two cycles. The subjects of the study were 33 students in grade XI IPS 1 SMA Negeri 2 Wonosari. Data collection was carried out through observation, documentation, interviews, and questionnaires. The collected data was analyzed using qualitative methods, such as data reduction, data presentation, and conclusion drawn, as well as quantitative methods that included the assessment of Accounting learning activities and students' responses to Think Pair Share learning. The observation results showed that there was an increase in the learning activities of Islamic Religious Education students from Cycle I to Cycle II in various aspects observed. In the aspect of reading material, there was an increase from 56.61% in Cycle I to 91.81% in Cycle II. For the aspect of asking questions, the percentage increased from 77.76% in Cycle I to 84.88% in Cycle II. The aspect of expressing opinions in group discussions increased from 59.66% to 82.83% in Cycle II, while the aspect of responding to other people's opinions increased from 67.61% in Cycle I to 88.87% in Cycle II. In the aspect of paying attention, there was an increase from 60.61% in Cycle I to 76.73% in Cycle II. The note-making aspect showed a significant increase from 40.48% in Cycle I to 88.88% in Cycle II. In addition, group discussion activities increased from 62.65% in Cycle I to 95.96% in Cycle II, and the aspect of doing assignments remained stable at 86.87% in both cycles. Finally, the aspect of concern for group members increased sharply from 56.57% in Cycle I to 95.96% in Cycle II. This result was reinforced by interviews that showed that all indicators of student response to ditulis this learning model scored above 90%.